Gadolinium nanoparticles and contrast agent as radiation sensitizers. (19th May 2015) - Taupin, Florence; Flaender, Mélanie; Delorme, Rachel; Brochard, Thierry; Mayol, Jean-François; Arnaud, Josiane; Perriat, Pascal; Sancey, Lucie; Lux, François; Barth, Rolf F; Carrière, Marie; Ravanat, Jean-Luc; et al.
Abstract: The goal of the present study was to evaluate and compare the radiosensitizing properties of gadolinium nanoparticles (NPs) with the gadolinium contrast agent (GdCA) Magnevist ® in order to better understand the mechanisms by which they act as radiation sensitizers. This was determined following either low energy synchrotron irradiation or high energy gamma irradiation of F98 rat glioma cells exposed to ultrasmall gadolinium NPs (GdNPs, hydrodynamic diameter of 3 nm) or GdCA. Clonogenic assays were used to quantify cell survival after irradiation in the presence of Gd using monochromatic x-rays with energies in the 25 keV–80 keV range from a synchrotron and 1.25 MeV gamma photons from a cobalt-60 source. Radiosensitization was demonstrated with both agents in combination with X-irradiation. At the same concentration (2.1 mg mL −1 ), GdNPS had a greater effect than GdCA. The maximum sensitization-enhancement ratio at 4 Gy (SER4Gy ) was observed at an energy of 65 keV for both the nanoparticles and the contrast agent (2.44 ± 0.33 and 1.50 ± 0.20, for GdNPs and GdCA, respectively). At a higher energy (1.25 MeV), radiosensitization only was observed with GdNPs (1.66 ± 0.17 and 1.01 ± 0.11, for GdNPs and GdCA, respectively). The radiation dose enhancements were highly 'energy dependent' for both agents. Secondary-electron-emission generated after photoelectric events appeared to be the primary mechanism by which Gd contrast agents functioned as radiosensitizers. On the other hand, other biological mechanisms, such as alterations in the cell cycle may explain the enhanced radiosensitizing properties of GdNPs.